2023
DOI: 10.1186/s12903-023-02807-4
|View full text |Cite
|
Sign up to set email alerts
|

Hexokinase 2-mediated glycolysis supports inflammatory responses to Porphyromonas gingivalis in gingival fibroblasts

Abstract: Background When infected with Porphyromonas gingivalis, gingival fibroblasts undergo metabolic reprogramming, and rely on aerobic glycolysis rather than oxidative phosphorylation for rapid energy replenishment. Hexokinases (HKs) are catalysts for glucose metabolism, and HK2 constitutes the major HK inducible isoform. The objective of this study is to determine whether HK2-mediated glycolysis promotes inflammatory responses in inflamed gingiva. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The blockade of glycolysis suppressed the LPS-induced macrophage pyroptosis, resulting in an attenuation of the in ammatory response and bone resorption in periodontitis [40]. It was found that HK2-mediated glycolysis promoted in ammatory responses in human gingival broblasts in gingival tissues [41]. Speci cally, this study determined that the mRNA expressions of glycolysis related genes HK1, HK2, and PFKFB3, which were upregulated in periodontal tissues.…”
Section: Discussionmentioning
confidence: 70%
“…The blockade of glycolysis suppressed the LPS-induced macrophage pyroptosis, resulting in an attenuation of the in ammatory response and bone resorption in periodontitis [40]. It was found that HK2-mediated glycolysis promoted in ammatory responses in human gingival broblasts in gingival tissues [41]. Speci cally, this study determined that the mRNA expressions of glycolysis related genes HK1, HK2, and PFKFB3, which were upregulated in periodontal tissues.…”
Section: Discussionmentioning
confidence: 70%
“…P. gingivalis , strain ATCC 33277, was maintained in the brain heart infusion broth, with supplement of yeast extract (1 mg/ml), hemin (5 mg/ml) and menadione (1 mg/ml) in an anaerobic condition (85 % N 2 , 5 % H 2 , and 10 % CO 2 ) at 37 °C. Bacterial levels were normalized using a spectrophotometer (SpectraMax M3, USA) to an optical density (OD) of 1 at 600 nm, equivalent to 10 9 CFU/ml [ 25 ]. P. gingivalis infected OCCM-30 cells at the exponential growth phase with varying multiplicity of infection (MOI = 30, 100 and 300) as detailed in the figure captions.…”
Section: Methodsmentioning
confidence: 99%